2015
DOI: 10.1161/atvbaha.114.305150
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic Effects of Transforming Growth Factor-β Signaling During Aortic Aneurysm Progression in Mice Suggest a Combinatorial Therapy for Marfan Syndrome

Abstract: Objective Studies of mice with mild Marfan syndrome (MFS) have correlated the development of thoracic aortic aneurysm (TAA) with improper stimulation of non-canonical (Erk-mediated) TGFβ signaling by the angiotensin type I receptor (AT1r). This correlation was largely based on comparable TAA modifications by either systemic TGFβ neutralization or AT1r antagonism. However, subsequent investigations have called into question some key aspects of this mechanism of arterial disease in MFS. To resolve these controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
298
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(314 citation statements)
references
References 27 publications
15
298
1
Order By: Relevance
“…Studies conducted in MFS mouse models have suggested that effects of TGF-b signaling attenuation with neutralizing antibodies are dependent on the developmental stage of the vessel wall, with early TGF-b inhibition, between three and six weeks of age, being deleterious, and late TGF-b inhibition, after 6 weeks of age, being beneficial (Cook et al 2015). These observations are consistent with the studies discussed above suggesting that TGF-b signaling has a protective role prenatally and perinatally, when it is required to complete vessel wall development and elastogenesis, and a pathogenic role after such events are completed.…”
Section: Marfan Syndromementioning
confidence: 99%
“…Studies conducted in MFS mouse models have suggested that effects of TGF-b signaling attenuation with neutralizing antibodies are dependent on the developmental stage of the vessel wall, with early TGF-b inhibition, between three and six weeks of age, being deleterious, and late TGF-b inhibition, after 6 weeks of age, being beneficial (Cook et al 2015). These observations are consistent with the studies discussed above suggesting that TGF-b signaling has a protective role prenatally and perinatally, when it is required to complete vessel wall development and elastogenesis, and a pathogenic role after such events are completed.…”
Section: Marfan Syndromementioning
confidence: 99%
“…Results of this study provide important new information for our understanding of the role that both systemic and localized tissue inflammation play in these life threatening pathologies of the aortic vessel wall. In addition, results of this and other studies (23) point to significant differences in mechanisms of aortic dissection linked to genetic diseases such as Marfan syndrome, in which TGFβ and its downstream intracellular signaling molecules Smad2/3 and ERK1/2, have important, causal roles in the vessel wall dissections (24,25).…”
Section: Experimental Modelsmentioning
confidence: 58%
“…It is worth noting that the outer laminae orientation of ascending aortic pathology is not a unique feature in Ang II-infused mice. This feature has been frequently observed in many animal models in which ascending aortic aneurysmal diseases are provoked by a wide variety of stimuli (7,(15)(16)(17). Of clinical relevance, the predominance of pathology in the outer medial layers is also a common feature in human ascending aortic aneurysm and dissection (14,18).…”
Section: Commentarymentioning
confidence: 80%
“…Although there are multiple genetic disruptions that lead to ascending aortic aneurysms and dissection, these diseases can be mimicked by manipulations in animal models. It is worth noting that angiotensin II (Ang II) and its type 1 (AT1) receptor activation contribute to the development and progression of ascending aortic pathologies in all of these animal models (2)(3)(4)(5)(6)(7). Ascending aortic aneurysms are one risk factor for aortic dissection.…”
mentioning
confidence: 99%